Cognitive Inflexibility in Gamblers is Primarily Present in Reward-Related Decision Making - Boog, Michiel; Höppener, Paul; v. d. Wetering, Ben J. M.; Goudriaan, Anna E.; Boog, Matthijs C.; Franken, Ingmar H. A. (Frontiers in Human Neuroscience, 2014)
One hallmark of gambling disorder is the observation that gamblers have problems stopping their gambling behavior once it is initiated. On a neuropsychological level it has been hypothesized that this is the result of a cognitive inflexibility. The present study investigated cognitive inflexibility in patients with gambling disorder using a task involving cognitive inflexibility with a reward element (i.e., reversal learning) and a task measuring general cognitive inflexibility without such a component (i.e., response perseveration). For this purpose, scores of a reward-based reversal learning task (Probabilistic Reversal Learning Task) and the Wisconsin Card Sorting Task were compared between a group of treatment seeking patients with gambling disorder and a gender and age matched control group. The results show that pathological gamblers have impaired performance on the neurocognitive task measuring reward based cognitive inflexibility. However, no difference between the groups is observed regarding non-reward based cognitive inflexibility. This suggests that cognitive inflexibility in gambling disorder is the result of an aberrant reward-based learning, and not based on a more general problem with cognitive flexibility. The pattern of observed problems is suggestive of a dysfunction of the orbitofrontal cortex, the ventrolateral prefrontal cortex and the ventral regions of the striatum in gamblers. Relevance for the neurocognition of problematic gambling is discussed.